Molecular dynamics calculations of heat conduction in actinide oxides under thermal gradient. (November 2015) - Matsumoto, Taku; Arima, Tatsumi; Inagaki, Yaohiro; Idemitsu, Kazuya; Kato, Masato; Uchida, Teppei
Abstract: Thermal conductivities of UO2, PuO2 and (U0.8, Pu0.2 )O2 have been investigated by non-equilibrium molecular dynamics (NEMD) simulation between 300 K and 2000 K. The thermal conductivity was directly calculated by the temperature gradient on the system according to Fourier's law in NEMD simulation. The thermal conductivity obtained from the NEMD simulation decreases with a decrease of the supercell size, which means the phonon scattering occurs at the system boundaries in the microsystem. In addition, the present NEMD simulation, as well as previous EMD simulation studies, clearly shows that the Umklapp process causes the decrease of thermal conductivity at high temperatures. When comparison is made with literature data, the calculated results obtained from the relatively small supercell are in good agreement with the measured ones for the above actinide dioxides. Highlights: The thermal conductivities of UO2, PuO2 and MOX have been investigated by non-equilibrium molecular dynamics (NEMD) method. The calculated results decreased with a decrease of the supercell size. The calculated results obtained from the relatively small supercell were in good agreement with literature data. The calculated thermal conductivities were fairly close among UO2, PuO2 and MOX.